Phylogenetic distribution of TTAGG telomeric repeats in insects - Frydrychová, Radmila; Grossmann, Petr; Trubac, Pavel; Vítková, Magda; Marec, Frantisek (Genome, 2004)
We examined the presence of TTAGG telomeric repeats in 22 species from 20 insect orders with no or inconclusive information on the telomere composition by single-primer polymerase chain reaction with (TTAGG)6 primers, Southern hybridization of genomic DNAs, and fluorescence in situ hybridization of chromosomes with (TTAGG)n probes. The (TTAGG)n sequence was present in 15 species and absent in 7 species. In a compilation of new and published data, we combined the distribution of (TTAGG)n telomere motif with the insect phylogenetic tree. The pattern of phylogenetic distribution of the TTAGG repeats clearly supported a hypothesis that the sequence was an ancestral motif of insect telomeres but was lost repeatedly during insect evolution. The motif was conserved in the "primitive" apterous insect orders, the Archaeognatha and Zygentoma, in the "lower" Neoptera (Plecoptera, Phasmida, Orthoptera, Blattaria, Mantodea, and Isoptera) with the exception of Dermaptera, and in Paraneoptera (Psocoptera, Thysanoptera, Auchenorrhyncha, and Sternorrhyncha) with the exception of Heteroptera. Surprisingly, the (TTAGG)n motif was not found in the "primitive" pterygotes, the Palaeoptera (Ephemeroptera and Odonata). The Endopterygota were heterogeneous for the occurrence of TTAGG repeats. The motif was conserved in Hymenoptera, Lepidoptera, and Trichoptera but was lost in one clade formed by Diptera, Siphonaptera, and Mecoptera. It was also lost in Raphidioptera, whereas it was present in Megaloptera. In contrast with previous authors, we did not find the motif in Neuroptera. Finally, both TTAGG-positive and TTAGG-negative species were reported in Coleoptera. The repeated losses of TTAGG in different branches of the insect phylogenetic tree and, in particular, in the most successful lineage of insect evolution, the Endopterygota, suggest a backup mechanism in the genome of insects that enabled them frequent evolutionary changes in telomere composition.
Keywords: telomery; druhová specificita; Insecta; In Situ Hybridization, Fluorescence; Animals; Southernův blotting; DNA primery; hybridizace in situ fluorescenční; Species Specificity; Tandem Repeat Sequences; hmyz; DNA Primers; konzervovaná sekvence; tandemové repetitivní sekvence; Telomere; zvířata; fylogeneze; Conserved Sequence; Phylogeny; Blotting, Southern